Case Report: Approaches for managing resistant cytomegalovirus in pediatric allogeneic hematopoietic cell transplantation recipients - Song, Eunkyung (Frontiers in Pediatrics, 2024)
We present a pediatric haploidentical TCRαβ+/CD19+ depleted allogeneic hematopoietic cell transplantation recipient who developed early onset CMV infection, which was complicated by resistant CMV (both UL97 and UL54) and successfully managed with maribavir and haploidentical CMV-specific T lymphocytes. We illustrate novel approaches to resistant CMV and highlight the effective utilization of recent advances in diagnosis and management of resistant CMV in pediatric HCT.